Removal of chlorpyrifos using micelle–clay complex and advanced treatment technology. Issue 33 (14th July 2016) - Qurie, Mohannad; Khamis, Mustafa; Ayyad, Ibrahim; Scrano, Laura; Lelario, Filomena; Bufo, Sabino Aurelio; Mecca, Gennaro; Karaman, Rafik
Abstract: In this study, the stability of chlorpyrifos, a known pesticide, in fresh water and sludge was investigated. The results showed that chlorpyrifos underwent hydrolysis in both media to give two main metabolites: 3, 5, 6-trichoro-2-pyridiniol (TCP) and diethylthiophosphoric acid (DETP). The hydrolysis reaction in both media was found to follow first-order kinetics with a rate constant of 7.10 × 10 −8 ( R 2 = 0.999) in pure water and of 9.30 × 10 −8 ( R 2 = 0.996) in sludge. Chlorpyrifos degradation's half-life value in pure water was 112 d and in sludge was 85.9 d. The efficiency of Al-Quds University wastewater treatment plant demonstrated that the ultrafiltration-hollow fiber unit (UF-HF) was insufficient in removing chlorpyrifos from spiked secondary treated wastewater samples, whereas the combination of ultrafiltration-spiral wound unit (UF-SW) followed by activated carbon (AC) column was quite efficient and yielded a complete removal of the pesticide. Batch adsorption experiments using either AC or micelle–clay complex were performed and the experimental results were fitted to Langmuir and Freundlich isotherms. Adsorption analysis using Langmuir isotherm revealed that Q max for the AC was higher than that of the micelle–clay complex, while Freundlich isotherm showed almost similar values of n (3.413 vs. 3.745) for both adsorbents, despite the fact that the activated carbon filter showed higher k F value. Filtration column of mixed micelle–clay complex and sand demonstrated a breakthrough point after the third fraction for chlorpyrifos removal and a complete removal for all fractions collected in the TCP experiment. This result reveals that mixed micelle–clay complex and sand column is much more efficient in removing TCP than removing its parent compound, chlorpyrifos.